Cross sectional association between cognitive frailty and disability among community-dwelling older adults: Focus on the role of social factors - Choi, Kyungwon; Ko, Young (Frontiers in Public Health, 2023)
Background This study aimed to investigate the prevalence of cognitive frailty and the influence of social factors on the association between different levels of cognitive frailty and disability. Methods A nationally representative survey of non-institutionalized community-dwelling older adults in Korea was used. A total, 9,894 older adults were included in the analysis. We assessed the effects of social factors using social activities, social contacts, living arrangements, emotional support, and satisfaction with friends and neighbors. Results The prevalence of cognitive frailty was 1.6%, which was consistent with other population-based studies. Hierarchical logistic analysis demonstrated that the association between different levels of cognitive frailty and disability was attenuated when social participation, social contact, and satisfaction with friends and community were included in the model, and the magnitude of these effects differed across the levels of cognitive frailty. Discussion Considering the influence of social factors, interventions to enhance social relationships can help slow down the progression of cognitive frailty to disability.